Kemeruapan pulangan pasaran indeks syariah Kuala Lumpur (KLSI): analisis model GARCH - Abu Bakar, Abu Sufian; Abdullah, Hussin; Shakrani, Mohd Saharudin; Mohd Taib, Hasniza (Universiti Utara Malaysia, 2004)
Volatility of stock returns can be defined as a dispersion of stock return mean, which is known as variance. Information and knowledge about the behaviour of stock return volatility is pertinently important to economists and financial analysts in order to solve related economic problems. Poterba and Summers(1986) relate the influence of continuous volatility in relation with changes in stock price volatility, while Bollerslev, Chou and Kroner, (1992) mentioned that there are three factors that influence the volatility behaviour which are continuous volatility, means-variance and asymmetric relationship. This research used the ARCH family model in analysing the volatility of "syariah" compliant stock return at BSKL because of its importance in analysing and predicting volatility. Empirical estimators used were syariah compliant stock prices for every counter, volume trading, Dow Jones Industrial Index, Syariah Index, Composite Index, lnterbank Interest Rate and Islamic Interbank Interest Rates. The research duration was from 2 January 1995 to 13 June 2003. The duration was then divided into two periods with the first period starting from 2 January 1995 to 29 April 1999, which was before the launch of syariah compliant stock. The second was after the launch of syariah compliant stock from 30 April 1999 to 13 June 2003.